A new satellite RNA is associated with natural infections of cucumber mosaic virus in succulent snap bean - Nouri, Shahideh (Springer Vienna, 2011)
Cucumber mosaic virus (CMV) was consistently recovered from symptomatic snap bean plants during surveys conducted in 2007 and 2008 in central Wisconsin. A large proportion of these CMV-infected plants contained a single-stranded linear RNA molecule consisting of 339 nucleotides and sharing 90–94% sequence identity with other satellite (sat) RNAs of CMV. Comparison of this satRNA sequence with currently available CMV satRNA sequences suggests this to be a novel satRNA.